Scenarios for investment of proposed marshes and requirements for success:a case study in the Marshlands of maysan - السوداني, علي موات; عباس, احمد جاسب (Journal of Economics and Administrative Sciences, 2018)
The research aims to presenting a number of scenarios for the investment of the marshes. The problem of research problem was that there is no in-depth analysis of the marshes  environment. The traditional methods of  the environmental analysis are insufficient. The research community is represented by the decision makers in Maysan Governorate. The research led to proposing of three scenarios with statement  the requirements for the success of each one. The most important conclusions are that the three proposed scenarios for marshes investment depend on the availability of the required volunteers for each scenario. The higher the availability of the requirements, the more optimistic the scenario becomes. If the requirements are met at an average level, The scenario is moderate, and if the requirements are at a weak level, the scenario is pessimistic, through the responses of the sample to the questionnaire. The most important recommendations are that the scenario forming process is supportive of the institutions to be prepared and more flexible and adaptable to the future in a dynamic environment. Pay attention to finding specialized cadres capable of carrying out this task.